2002
DOI: 10.1515/jpem.2002.15.2.139
|View full text |Cite
|
Sign up to set email alerts
|

SHOX Intragenic Microsatellite Analysis in Patients with Short Stature

Abstract: Background: SHOX haplo-insufficiency is considered the molecular basis of short stature in patients with Turner's syndrome, and gives rise to the short stature with mesomelic dysplasia and Madelung deformity of patients with Leri-Weill syndrome. Objective: Analysis of the intragenic SHOX microsatellite to define its utility in detecting SHOX haplo-insufficiency in patients with short stature. Patients and Methods: 207 patients with short stature (57 girls with Turner's syndrome [TS] [24 mosaicisms]; 73 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…Table 3 summarizes the published data in patients with SHOX haploinsufficiency treated with rhGH. 42,[66][67][68][69] The data are not complete in all cases and there was a wide range of rhGH dose. No ad- 68 demonstrated short-term benefit from rhGH therapy, with a mean improvement in height SDS of 0.8 at 12 months (n=8) and 0.6 at 24 months (n=3).…”
Section: Treatment Perspectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…Table 3 summarizes the published data in patients with SHOX haploinsufficiency treated with rhGH. 42,[66][67][68][69] The data are not complete in all cases and there was a wide range of rhGH dose. No ad- 68 demonstrated short-term benefit from rhGH therapy, with a mean improvement in height SDS of 0.8 at 12 months (n=8) and 0.6 at 24 months (n=3).…”
Section: Treatment Perspectivesmentioning
confidence: 98%
“…42 Clement-Jones and colleagues 15 suggested a possible involvement of SHOX-related growth impairment in the expression of other Turner stigmata such as high-arched palate, abnormal auricular development, cubitus valgus, genu valgum and short metacarpals. Other clinical investigators 39,43,44 reported that SHOX haploinsufficiency could lead to additional Turner skeletal abnormalities such as mesomelia and Madelung deformity.…”
Section: Implications Of Shox Gene Mutationsmentioning
confidence: 99%
“…Desde a descrição do papel do gene SHOX no crescimento e desenvolvimento ósseo e do reconhecimento que ele codifica um fator de transcrição expressado em células osteogênicas e em outros tecidos, vários trabalhos têm sido descritos associando mutações e deleções desse gene em 1 a 2,4% de crianças diagnosticadas como portadoras de baixa estatura idiopática (8,11,12,17,21,23,41).…”
Section: Arq Bras Endocrinol Metab Vol 47 Nº 6 Dezembro 2003unclassified
“…Outros autores também têm reforçado a importância de complementar o exame clínico na busca de sinais clínicos e radiológicos achados na ST nas crianças com diagnóstico de BEI (15,19,41).…”
Section: Arq Bras Endocrinol Metab Vol 47 Nº 6 Dezembro 2003unclassified
See 1 more Smart Citation